Ready, Set…Poised!: Polycomb target genes are bound by poised RNA polymerase II throughout differentiation - Alvaro Rada‐Iglesias (Molecular Systems Biology)
Abstract In embryonic stem cells (ESCs), silent genes with major developmental functions display a unique epigenetic state in which strong and broad binding by Polycomb repressive complexes (PRCs) is accompanied by the presence of poised RNA polymerase II (RNAPII) and activating histone marks (e.g. H3K4me3) (Azuara et al, 2006; Bernstein et al, 2006; Stock et al, 2007; Brookes et al, 2012). It has been suggested that the plasticity and broad differentiation potential of pluripotent cells might rely, at least partly, on this unique epigenetic state (Bernstein et al, 2006; Stock et al, 2007). In their recent study, Pombo and colleagues (Ferrai et al, 2017) show that a similar epigenetic state can be found at a subset of major developmental genes throughout the differentiation of ESCs into neurons, providing novel and exciting insights into the molecular basis of cellular plasticity in differentiated cells.